Factors Affecting Loan Quality on Sharia Fintech Lending Platforms: A Case Study In Indonesia - Wirdhatul Jannah Dasri; Wiku Suryomurti; Ang Soon Yong (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to see the Factors Affecting Loan Quality on Sharia Fintech Lending in Indonesia. This research uses a qualitative method of case studies by collecting secondary data through from OJK. This article looks at the Factors of current loans and non-current loans starting in early 2021 to 2023 for Sharia FinTech in Indonesia by adopting the multiple linear regression method and dummy variables to analyze data on more than two free variables. The estimates show factors for gender, age and domicile in FinTech lending in Indonesia. Furthermore, gender does not appear to significantly impact the number of loan recipients or the outstanding loan amount, age and domicile variables have a significant impact on these factors. Age categories show a positive impact on the number of loan recipients and the outstanding loan amount. Meanwhile, individuals outside of Java are more likely to be loan recipients compared to individuals in Java. These findings recommend that financial services authorities intensively encourage new innovative Sharia FinTech business models for lending to expand digital financial inclusion by providing financing for people (P2P) who are not touched by banks.